Natural Killer T Cell-Targeted Immunotherapy Mediating Long-term Memory Responses and Strong Antitumor Activity - Dashtsoodol, Nyambayar; Shigeura, Tomokuni; Tashiro, Takuya; Aihara, Minako; Chikanishi, Toshihiro; Okada, Hiromi; Hanada, Keigo; Sano, Hirokazu; Kurogi, Akihiko; Taniguchi, Masaru (Frontiers in Immunology, 2017)
Current tumor therapies, including immunotherapies, focus on passive eradication or at least reduction of the tumor mass. However, cancer patients quite often suffer from tumor relapse or metastasis after such treatments. To overcome these problems, we have developed an NKT cell-targeted immunotherapy focusing on active engagement of the patient’s immune system, but not directly targeting the tumor cells themselves. Natural Killer T (NKT) cells express an invariant antigen receptor α chain encoded by Trav11 (Vα14)-Traj18 (Jα18) gene segments in mice and TRAV10 (Vα24)-TRAJ18 (Jα18) in humans and recognize glycolipid ligand in conjunction with a monomorphic CD1d molecule. The NKT cells play a pivotal role in the orchestration of antitumor immune responses by mediating adjuvant effects that activate various antitumor effector cells of both innate and adaptive immune systems and also aid in establishing a long-term memory response. Here, we established NKT cell-targeted therapy using a newly discovered NKT cell glycolipid ligand, RK, which has a stronger capacity to stimulate both human and mouse NKT cells compared to previous NKT cell ligand. Moreover, RK mediates strong adjuvant effects in activating various effector cell types and establishes long-term memory responses, resulting in the continuous attack on the tumor that confers long-lasting and potent antitumor effects. Since the NKT cell ligand presented by the monomorphic CD1d can be used for all humans irrespective of HLA types, and also because NKT cell-targeted therapy does not directly target tumor cells, this therapy can potentially be applied to all cancer patients and any tumor types.